Upaya Pencegahan Stunting Di Kelurahan Pasar Kliwon - Wijayanti, Kenfitria Diah; Risyad, Afdharu; Fitriasiwi, Ade Hamrat; Almaas, Ainanur Fauziyah; Hidayati, Eka Nur; Rahma, Maysti Aulia; Supriani, Yuniati; Ramadhani, Azizah Rahmah Putri; Pangrokti, Ade Nining; Maharani, Kinanthi; Annisyah, Nurul (Society : Jurnal Pengabdian Masyarakat, 2022)
Stunting cases still often occur in the city of Surakarta, so the 'Sigrak Centingan' program was formed as an effort to reduce stunting. The program is running well, as evidenced by the data obtained there has been a decrease in the absence of stunting cases, especially in Pasar Kliwon Village. Based on this, the service carried out by Devotion Â 01 team aims to increase awareness of stunting and its prevention. Factors causing stunting in the Pasar Kliwon area are nutritional intake and low awareness of PHBS (Clean and Healthy Living Behavior). Devotion 01 team collaborates with posyandu cadres, PKK, residents, and local government through various work programs that can be carried out, including stunting socialization, posyandu, distribution of blood-added tablets, PHBS (Clean and Healthy Living Behavior), planting vegetable seeds, healthy Sunday, and waste reduction through eco-bricks. The results of the implementation of the work program indicate that the residents of Pasar Kliwon Village, especially young women, prospective brides, pregnant women, childbirth mothers, and breastfeeding mothers better understand the dangers of stunting and stunting prevention efforts can be carried out independently as early as possible.